Adrenomedullary progenitor cells: isolation and characterization of a multi-potent progenitor cell population - Vukicevic, Vladimir; Rubin de Celis, Maria Fernandez; Pellegata, Natalia S.; Bornstein, Stefan R.; Androutsellis-Theotokis, Andreas; Ehrhart-Bornstein, Monika (Elsevier, 2015)
The adrenal is a highly plastic organ with the ability to adjust to physiological needs by adapting hormone production but also by generating and regenerating both adrenocortical and adrenomedullary tissue. It is now apparent that many adult tissues maintain stem and progenitor cells that contribute to their maintenance and adaptation. Research from the last years has proven the existence of stem and progenitor cells also in the adult adrenal medulla throughout life. These cells maintain some neural crest properties and have the potential to differentiate to the endocrine and neural lineages. In this article, we discuss the evidence for the existence of adrenomedullary multi potent progenitor cells, their isolation and characterization, their differentiation potential as well as their clinical potential in transplantation therapies but also in pathophysiology.